GASTRONOMY'S INFLUENCE ON CHOOSING CULTURAL TOURISM DESTINATIONS: A STUDY OF GRANADA, SPAIN - Franklin CORDOVA-BUIZA; Lucía GARCÍA-GARCÍA; Lucía CASTAÑO-PRIETO; José VALVERDE-RODA (Geo Journal of Tourism and Geosites)
The growing importance of gastronomy in travel decisions has made it a key factor in selecting cultural tourism destinations. This research analyzes tourists' interest in Granada's cuisine, a city with two UNESCO World Heritage Sites. Fieldwork involved 1,612 validated surveys from tourists in various local gastronomy establishments. Analysis revealed three tourist segments based on their interest in gastronomy: survivors, enjoyers, and experiencers. Survivors view gastronomy as a minor part of their experience, enjoyers appreciate it as part of their cultural immersion, and experiencers seek unique culinary adventures. Key findings indicate that different tourist types have distinct characteristics and perceptions of local cuisine as a cultural identity symbol. Understanding these segments helps in tailoring tourism offerings to meet diverse preferences. This research underscores the significance of innovative culinary offerings and improved facilities to enhance tourism competitiveness. Consequently, it is crucial to develop strategies that promote gastronomic innovation and improve service quality in order to attract and satisfy a broader range of tourists.